Diglosia dalam Bahasa Arab: Kajian Sosiolinguistik - Cintia; Almita Wiguna (CENDEKIA INDONESIA, 2024)
Arabic is one of the languages ​​that experiences the diglossia phenomenon. Even so, this phenomenon is rarely discussed. In fact, a deep understanding of diglossia will help someone in learning Arabic. Therefore, researchers are interested in examining the concept of diglossia in Arabic. This research uses a qualitative approach. Data was obtained through literature review techniques with descriptive analysis. The data is in the form of formal Arabic and everyday language that is often used in Arab society. The research results show that diglossia refers to the use of two variations of language for different purposes and situations. Diglossia in Arabic occurs due to interaction with outside society and causes language mixing.